Measured Analysis on Surface Deformation and Influence of Cutter Torque for Twin Shield Tunnelling in Silty Sand - Yuqing Dong; Zhi Ding; Yexiang Jiang; Chunlai Chen; Wenming Shen; Yinze Wang (Advances in Civil Engineering)
In this study, the field measurement was conducted on the twin shield tunnelling in a shield section of Hangzhou Metro Line 6, where the surface deformation caused by twin shield tunnelling in the silty sand was obtained. The surface deformation law and the applicability of the twin-line Peck formula in the silt area were analyzed. The relationship between the cutterhead torque and the surface deformation in the silty sand was identified. Furthermore, the differences in surface deformation of twin shield tunnelling in the Hangzhou soft soil area were discussed. The results show that the settlement process caused by twin shield tunnelling in silty sand is faster than that of soft soil and has no rebound phenomenon. The twin-line Peck formula is suitable in silty sand, but the prediction of the latter line using this formula is slightly deviated because of the secondary disturbance effect. Due to the secondary disturbance of the soil caused by the construction of the latter line, the soil loss rate of the latter line is higher than that of the former line. Therefore, the reference ratio of the soil loss rate of the latter line and the former line is given. Furthermore, the cutterhead torque of the shield machine was found to be associated with the maximum instantaneous value of the surface deformation.